2015
DOI: 10.1038/ncomms9247
|View full text |Cite
|
Sign up to set email alerts
|

Critical heat flux maxima during boiling crisis on textured surfaces

Abstract: Enhancing the critical heat flux (CHF) of industrial boilers by surface texturing can lead to substantial energy savings and global reduction in greenhouse gas emissions, but fundamentally this phenomenon is not well understood. Prior studies on boiling crisis indicate that CHF monotonically increases with increasing texture density. Here we report on the existence of maxima in CHF enhancement at intermediate texture density using measurements on parametrically designed plain and nano-textured micropillar surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(162 citation statements)
references
References 54 publications
4
157
0
1
Order By: Relevance
“…We can explain this phenomenon by the fact that microropes are not perpendicular to the surface, and have a different angle of inclination. In addition, it was observed that the droplets on the surface have a very large imbibition layer [11]. We assume that water penetrate easily into grooves constituting the relief in case of Cassie impregnating wetting [12].…”
Section: Resultsmentioning
confidence: 99%
“…We can explain this phenomenon by the fact that microropes are not perpendicular to the surface, and have a different angle of inclination. In addition, it was observed that the droplets on the surface have a very large imbibition layer [11]. We assume that water penetrate easily into grooves constituting the relief in case of Cassie impregnating wetting [12].…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in solid-liquid contact area means that the heat flux required to generate the supporting vapour layer required for a Leidenfrost state has to be transferred through the reduced contact area between the liquid and the solid wires. This would mean that a higher temperature is needed for the required heat flux to generate a continuous vapour and so produce a Leidenfrost state [21][22][23][24]. Figure 2(b), degrades the fit, suggesting that this area is not a significant factor.…”
Section: Meshmentioning
confidence: 99%
“…Extensive research works have been carried out for improving boiling heat transfer performance, and they are generally classified into active, passive, and compound techniques [6]. The passive heat transfer enhancement techniques are usually used for improving the boiling heat transfer performance, because by using (2) where D d is the departure diameter, ∅ is the receding contact angle, γ is the surface tension, g is the acceleration due to gravity, and ρ L and ρ G are the liquid and vapor density, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Phase change heat transfer systems, such as pool and flow boiling heat sinks, are used extensively in the fields of refrigeration, air conditioning, and electronic devices cooling [1][2][3]. During the boiling heat transfer, the working fluid can absorb a large amount of heat with a small wall superheat due to its large latent heat of vaporization [4,5].…”
Section: Introductionmentioning
confidence: 99%